An optimized form-finding method of an asymmetric large deployable reflector. (15th February 2019) - Maddio, P.D.; Meschini, A.; Sinatra, R.; Cammarata, A.
Highlights: Form finding of asymmetric large deployable reflectors. Modified force density method. Elastic deformation of truss support and net system is taken into account. Abstract: Deployable mesh reflector antennas are widely used for space applications and the form-finding analysis plays an important role to reach the high surface accuracy. In this paper, an optimized algorithm extends the traditional force density method for the form-finding analysis of an asymmetric offset antenna. The optimization problem is solved by minimizing the RMS error with respect to the ideal paraboloid. First, the algorithm is implemented considering rigid ring truss support. Then, the effect of the elastic deformation of truss support is taken into account. The minimum distance between each free node of the front net and the ideal surface is used for the calculation of the RMS error. Finally, a numerical example is carried out to demonstrate the validity of the proposed method.